Implementasi Aplikasi Pengenalan Objek Wisata Di Provinsi Kalimantan Utara Berbasis Android - Azidan, Fikriansyah; Aji, Adam Sekti (STMIK Banjarbaru, 2024)
The tourism introduction application for North Kalimantan province is a solution that aims to help individuals or groups, especially tourists from outside the province, to find out about and visit tourist attractions or tourist attractions in North Kalimantan province. In an effort to increase efficiency in helping Micro, Small and Medium Enterprises (UMKM) carried out by the community, mobile applications are used as a method that creates a more interactive and interesting experience. The use of mobile applications in applications for recognizing tourist attractions in North Kalimantan province involves smartphone or tablet-based devices. This application allows users to see descriptions and locations of tourist attractions they will visit. In this study, Blackbox testing was carried out which resulted in the finding that the application features functioned well overall. This application helps people who want to visit North Kalimantan province to easily find tourist destinations to visit.Keywords: Smartphone; Tour; North Kalimantan; Micro Small and Medium Enterprises; TouristÂ AbstrakAplikasi pengenalan wisata provinsi Kalimantan Utara merupakan solusi yang bertujuan membantu individu atau kelompok, terutama wisatawan dari luar provinsi, untuk mengetahui dan mengunjungi tempat wisata atau objek wisata di provinsi Kalimantan utara. Dalam usaha meningkatkan efisiensi dalam membantu Usaha Mikro Kecil Menengah (UMKM) yang dilakukan oleh masyarakat, Aplikasi mobile digunakan sebagai metode yang menciptakan pengalaman yang lebih intraktif dan menarik. Pengunaan aplikasi mobile dalam aplikasi pengenalan objek wisata provinsi Kalimantan utara melibatkan perangkat berbasis smarthphone atau tablet. Aplikasi ini memungkinkan penguna untuk melihat deskripsi dan lokasi dari tempat wisata yang akan di datangi. Dalam sutudi ini, dilakukan pengujian Blackbox yang menghasilkan temuan bahawa fitur aplikasi berfungsi dengan baik secara keseluruhan. Aplikasi ini membantu masyarakat yang ingin berkunjung ke provinsi Kalimantan Utara dengan mudah untuk menemukan destinasi wisata yang akan dikunjungi.Â